OBSERVATION OF XI-,XI-BAR- PRODUCTION IN E+E- ANNIHILATION - Althoff, M; Braunschweig, W; Gather, K; Kirschfink, F; Lubelsmeyer, K; Martyn, H; Peise, G; Rimkus, J; Rosskamp, P; Sander, H; Schmitz, D; Siebke, H; et al. (1983)
We present evidence for the production of Ξ·-, Ξ- in e+e- annihilation into hadrons. Our measurements yields: 0.026 ± 0.008 (stat.) ± 0.009 (syst.) Ξ-,Ξ- per hadronic event at W ∼ 34 GeV. Using our previous measurements of Λ, Λ and p,p production we obtain the relative yields (Ξ-, Ξ-/(Λ, Λ = 0.087 ± 0.03 (stat.) ± 0.03 (syst.) and (Ξ-, Ξ-/(p, p = 0.033 ± 0.011 (stat.) ± 0.011 (syst.). © 1983.